Entrapment- und Non‑Entrapment-Syndrome am Ellenbogen - Godel, Tim; Pham, Mirko (Der Radiologe, 2018)
Clinical/methodical issue: Entrapment syndromes of peripheral nerves at the elbow are common and are often diagnostically challenging disorders. Difficulties consist in lesion localization and recognition of complex spatial lesion patterns as well as in differentiation of focal and multifocal disorders.Standard diagnostic methods: Medical history taking, neurological examination and neurophysiological tests represent the gold standard in the diagnosis of peripheral nerve lesions at the elbow, but have known methodical limitations. Methodical innovations: Additional diagnostic imaging tools recently developed for high-resolution visualization of extended peripheral nerve segments include 3 T magnetic resonance neurography (MRN) and neurosonography. Performance: MRN and neurosonography can directly visualize and thus precisely localize focal and nonfocal peripheral nerve lesions of various origins with high spatial resolution at the anatomical level of nerve fascicles. Achievements: MRN can cover peripheral nerve structures at the elbow, evaluate spatial nerve lesion patterns and partly disclose underlying causes. Practical recommendations: Imaging of peripheral nerves is a valuable addition in the diagnostic work-up of entrapment syndromes at the elbow and provides important assistance in the differentiation of nonfocal differential diagnoses, especially in cases that cannot be clarified using standard diagnostic methods. The evaluation of spatial nerve lesion pattern may give additional information on the origin of the underlying disease, which is essential for further treatment.
Gesehen am 08.05.2019